2016
DOI: 10.1097/qad.0000000000001015
|View full text |Cite
|
Sign up to set email alerts
|

Impaired gut junctional complexes feature late-treated individuals with suboptimal CD4+ T-cell recovery upon virologically suppressive combination antiretroviral therapy

Abstract: These observations establish gut damage and the size of the HIV reservoir as features of deficient immunological response to cART and provide new elements for interventional strategies in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 75 publications
5
53
1
Order By: Relevance
“…Because clinical and translational research strongly suggests that chronic activation of innate immunity drives morbidity/mortality in treated HIV (6468), our data provide in vitro evidence (tested in culture from both whole PBMCs and MDMs) of how monocyte/macrophages from cART patients might be preferentially activated by circulating bacterial products. Given the persistence of gut damage and microbial translocation during cART (9, 25, 26, 29, 69), we hereby provide an indication of how the systemic exposure to bacterial TLR agonists translocated from a damaged gut may contribute to excessive morbidity/mortality in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because clinical and translational research strongly suggests that chronic activation of innate immunity drives morbidity/mortality in treated HIV (6468), our data provide in vitro evidence (tested in culture from both whole PBMCs and MDMs) of how monocyte/macrophages from cART patients might be preferentially activated by circulating bacterial products. Given the persistence of gut damage and microbial translocation during cART (9, 25, 26, 29, 69), we hereby provide an indication of how the systemic exposure to bacterial TLR agonists translocated from a damaged gut may contribute to excessive morbidity/mortality in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, HIV-1 encodes for various TLR7/8 ligands that can mediate direct activation of the immune system in vitro (2224). Likewise, HIV-driven gut barrier damage is not reverted by cART (2528) and leads to the passage of microbial products in peripheral blood, mainly lipopolysaccharide (LPS), which is a TLR4 agonist (29, 30). Circulating LPS levels have been associated with immune activation both in treated and untreated HIV (3135); furthermore, exogenous in vivo LPS administration has been described to enhance immune activation (34).…”
Section: Introductionmentioning
confidence: 99%
“…showed that the level of HIV‐1 reservoirs, measured as the frequencies of cells harboring total and integrated HIV‐DNA as well as 2 long terminal repeat circles, in both peripheral CD4 + T cells and intestinal tissue was comparable between HIV‐1‐infected INRs and IRs. However, HIV reservoirs in both peripheral blood and the gut negatively correlate with CD4 + T‐cell reconstitution, suggesting that poor immune recovery on ART may be associated with increased HIV reservoirs . Agrati et al.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 99%
“…Total CD4 + T-cell count > 350 cells/µl and/or increase in the CD4 + T-cell count > 30% from baseline at 1-10 years after ART initiation, with an undetectable plasma VL. 144,177,242,243 Total CD4 + T-cell count < 500 cells/µl and CD4/CD8 ratio < 1 at 8 years after ART initiation, with plasma HIV RNA < 50 copies/ml.…”
Section: Definition Of "Immunological Nonresponder" Definition Of "Immentioning
confidence: 99%
“…Indeed, a reduced expression of ileum and colonic gut junctional complex proteins (cadherins, claudins, occludins) features long-term treated subjects [49][50][51] and is linked to increased gut permeability and persistent levels of microbial translocation [51]. Moreover, the negative correlation between LPS-dependent immune activation (sCD14 plasma levels, peripheral CD8 + CD38 + T-cell frequencies) and gut junctional proteins [49,51] further highlights that GI tract defects may contribute to inflammation. In line with this finding, a cohort study showed that peripheral blood levels of intestinal fatty acid binding protein, marker of intestinal damage, and zonulin-1 are independent predictors of mortality in cART-treated subjects [52].…”
Section: More Recently Studies Have Shed Light On the Underlying Mecmentioning
confidence: 99%